In Vitro Micropropagation of Vitis Vinifera L. in Kurdistan Region of Iraq - Ahmed, Aveen M.N.; Ibrahim, Diaa A.; Uzun, Seyran P. (Science Journal of University of Zakho, 2015)
This investigation was carried out at plant biotechnology laboratories of Scientific Research Center in Faculty of Science, University of Duhok, Kurdistan Region of Iraq, during the period from April 2013 to January 2014. The objectives of the study were to investigate the influence of different plant growth regulators in micropropagation on two local cultivars of grapes Vitis vinifera L. The most effective explant disinfestations were obtained by using NaOCl in a ratio of 1:1 water for 10 min which was very effective in reducing contamination in the established cultures resulting in a higher percentage of contaminations free cultures. At initiation stage, the highest initiation rate was achieved by using specific concentrations of BA on basal MS media. At multiplication stage, BA alone and BA combined with GA3 which was showed different responses in the measured parameters. At rooting formation stage two auxins were tested including IAA and NAA to estimate their ability for root formation. The in vitro propagated of grape plantlets were gradually transferred in successful way from lab. To field conditions, which didn’t showed any morphological abnormalities